A Beacon of Space and Time: Detailed Depiction of Human Space in the Xiong'an New Area Guided by Material Cultural Heritages. (4th August 2021) - Cao, Yingchun; Yang, Jie; Chen, Xiaoling; Yang, Xiujuan
Abstract : In April 2017, the Chinese government announced a plan to establish a national new district: the Xiong'an New Area (hereinafter referred to as Xiong'an). Xiong'an plays a major role in optimizing the layout of Beijing-Tianjin-Hebei city cluster, promoting the rapid development of regional cities and cultivating new drivers of innovative economy. As a result, Xiong'an is recognized in China as a millennium plan and a project with national significance. At this time, the scientific and forward-looking preliminary research work from more different fields will become important support to ensure the healthy development of Xiong'an. Taking the material cultural heritages of Xiong'an as a beacon, this paper makes a detailed depiction of the forms and features of the human space in Xiong'an in different stages during the ancient times. Multiple instruments were combined to realize the depiction, including archeological methods, geographical methods, and sociological methods. The results show that, on the vast North China Plains, with Baiyangdian Lake as the center, different social, political, and cultural factors have a huge impact on the social conditions, humanities activities, and heritage survival. Finally, based on the existing heritages, a visual projection was established between the ancient human space and the spatial distribution of potential heritages and used to predict the probability distribution of potential heritages in Xiong'an. The research results provide a scientific and forward-looking guide for the protection of material cultural heritages in the upcoming massive construction of Xiong'an.